A social semiotic approach to textbook analysis: the construction of the discourses of Pharmacology - Weiss, Rachel; Archer, Arlene (Faculty of Education, University of the Free State, 2014)
This article takes a multimodal social semiotic approach to analysing educational textbooks. We are interested in the ways in which educational textbooks contribute to designing our social futures by constructing both the student and the discipline in a particular manner. While a textbook’s primary purpose is to provide the reader with knowledge content about a specific topic, it also serves to conventionalise and entrench certain discipline-specific practices and values. A textbook simultaneously competes in an economic environment where the reader has a choice of many textbooks. The text, therefore, takes on a hybrid form, where marketisation and conversationalisation co-exist in dialogue with academic discourse. The article analyses the discourses of Pharmacology as constructed in two widely used Pharmacology textbooks in South Africa. We take a systemic functional approach which views texts as realising meaning in three ways, namely the ideational, the interpersonal and the textual. The analysis shows how one of the textbooks tends to establish a more democratic relationship between authors and readers, while constructing Pharmacology within a scientific discourse of drugs. The other textbook constructs a more traditional and hierarchical relationship between author and reader, yet tends to reinforce a clinical, patient-centred approach to Pharmacology. We argue that this kind of analysis is important when interrogating curriculum, as textbooks are crucial sites of struggle over discourse, meaning and power.
Keywords: Social semiotics; Discourses of Pharmacology